GENETIC ANALYSIS OF TROPICAL MAIZE (ZEA MAYS L.) INBRED LINES UNDER HEAT STRESS - AKULA DINESH; AYYANAGOUDA PATIL (The Bioscan, 2024)
The present investigation was carried out with the objective of estimating the genetic variability, heritability and genetic advance of key traits in tropical maize inbred lines .Analysis of variance revealed significant differences among the inbred lines for all the characters studied except for cob length,The PCV values were greater than GCV values for all the characters indicating considerable influence of environment on the expression of traits. High magnitude of GCV and PCV values were reported for an the sissilking interval (32.27 and 47.68), pollen shed duration (70.3 and 106.38), 100 grain weight (20.97 and 27.49), shelling per cent (28.18 and 35.30), grains per cob (95.56 and 104.4) and grains yield per plant (113.99 and 135.84). Broad sense heritability ranged from 34 per cent for cob length to 89 per cent for number of days to male flowering. High heritability along with high genetic advance as per cent of mean was observed for ear height (73% and 22.71), cob girth (67% and 21.16), shelling per cent (64% and 46.28), grains per cob (84% and 180.19) and grain yield per plant (70% and 197.04), favoring simple selection for the traits in early generations for developing heat tolerant maize.